Causes and consequences of quack medicine in health care: a scoping review of global experience - Ali Amir-Azodi; Mohammad Setayesh; Mohammad Bazyar; Mina Ansari; Vahid Yazdi-Feyzabadi (BMC, 2024)
Abstract Background The field of health has been facing challenges with fraudulent practices and the prevalence of "quack medicine". Many cases have given rise to this issue. Therefore, this study aims to comprehensively investigate and categorize the causes and consequences of quack medicine in the healthcare. Methods A scoping review, using the 5 stages of Arksey and O'Malley's framework, was conducted to retrieve and analyze the literature. International databases including the PubMed, Scopus, Embase and Web of Science and also national Iranian databases were searched to find peer reviewed published literature in English and Persian languages. Grey literature was also included. Meta-Synthesis was applied to analyze the findings through an inductive approach. Results Out of 3794 initially identified studies, 30 were selected for this study. Based on the findings of this research, the causes of quackery in the health were divided into six categories: political, economic, socio-cultural, technical-organizational, legal and psychological. Additionally, the consequences of this issue were classified into three categories: health, economic and social. Economic and social factors were found to have a more significant impact on the prevalence of quackery in the health sector. Legal and technical-organizational factors played a crucial role in facilitating fraudulent practices, resulting in severe health consequences. Conclusion It is evident that governing bodies and health systems must prioritize addressing economic and social factors in combating quackery in the health sector. Special attention should be paid to the issue of cultural development and community education to strengthen the mechanisms that lead to the society access to standard affordable services. Efforts should be made also to improve the efficiency of legislation, implementation and evaluation systems to effectively tackle this issue.